Training on Using the Canva Digital Application for Teacher Creativity at SD Negeri 4 Jatijajar as a Teaching Aspiration - Arif Muhafid, Ervian; Fatmawati, Dewi; Nendi Nur Hilal, Farah; Novel Larasati, Hermas; Valentin Sasih, Sulistia; Puspa Ayu Wulandari, Meysin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
In this era whereas technology continues to develop rapidly like today, teachers must develop digital skills, especially in creating learning media because of teacher creativity in teaching aspirations. Training on using Canva was held to improve teachers' technology and digital literacy skills at SD Negeri 4 Jatijajar. By increasing teachers' technological skills and digital literacy, there is potential for continued innovation in the development of learning media. Developing interesting learning media can help students understand the material being taught because this service implementation uses lecture methods, questions and answers, and direct practice using the Canva application. The activity steps carried out in this community service activity include, 1) design stage, 2) training stage, 3) evaluation stage. Implementing this community service will ultimately provide additional insight to teachers in creating learning media using Canva creatively and innovatively.